Variations in nutrient foramina of clavicle - A descriptive study - Prerana Aggarwal; Sumi Ghorai (Wolters Kluwer Medknow Publications, 2021)
Background: Human clavicle, an important bone of the pectoral girdle connects the upper appendicular skeleton to the axial skeleton. The nutrition and growth of the bone depend mainly on the nutrient artery. It enters the bone through the nutrient foramen. Hence this study aimed to study the number, position, location, direction, and distance of nutrient foramina of the clavicle from the sternal end. Methodology: In a descriptive study 79 dry adult human clavicles (40 right, 39 left) were studied, and mean foramen index (FI) was calculated. The data obtained were tabulated, results obtained and the inference was drawn. Results: The mean length of clavicles studied was 141.36 ± 11.11 mm (right 140.51 ± 11.10 mm, left 142.36 ± 11.14 mm). The average distance of foramina (DNF) from the sternal end was 61.48 ± 15.82 mm (right 62.88 ± 16.28 mm, left 59.96 ± 15.12 mm). Nutrient foramen was found in all the studied bones. The total foramina observed are 120. Forty-four bones have single (55.70%), 29 double (36.71%), and 6 triple (7.59%) foramina. Foramina were distributed on all four surfaces of the clavicle, predominantly on the posterior surface (52.50%). Most foramina were present on the middle third (67.50%) with an average FI% of 43.82 ± 11.85 (right 44.99 ± 12.09, left 42.43 ± 11.41). The foramina were directed toward the acromial end in all cases. Conclusion: The nutrient artery of the clavicle needs to be preserved for maintaining its vitality. Hence, the morphometric and topographic knowledge related to nutrient foramen and its variations is of immense importance to orthopedic surgeons and radiotherapists while treating clavicular pathologies.